In-service teacher training in a professional development perspective: Logics of participation of teachers - Machado, Eusébio André (2018)
The main purpose of this study is to understand the reasons why teachers undertake in-service teachers training as a factor of professional development (PD). At a background level, it also aims at understanding teacher’s availability to take part in designing and implementing their own training courses and at defining the kind of impact that the current teachers’ working conditions and types of leaderships in Portuguese schools may have on teachers’ availability for training. It is an interpretative study belonging to the category of educational case studies and ethnographic studies. As participant observers, the researchers had the opportunity to understand the entire context, the elements that influenced the participants’ behaviour and to articulate them. The study was made in five schools which are associated to the Marco de Canaveses and Cinfães In-service Teachers Training Centre (ISTTC). The data collection and analysis techniques are the object of a detailed description in order to ensure both internal and external validity of the results obtained. The information in this study was collected in two different ways: by applying an enquiry to 450 teachers (N=450) in the five schools selected and by analysing the data previously collected within the process of asking teachers to evaluate teachers training courses organized by the ISTTC (218 enquiries analysed) (n=218). The main conclusions drawn from the study are that, although the working conditions at schools are by far worse than 3 or 4 years ago, teachers are still available to invest on their professional training to a certain extent both when it means spending money and when it means spending time and energy. Also a large majority of participants consider themselves active participants in the needs analysis process and then in the courses planning process that take place in their schools. Most of them believe that their classroom practice improves after in-service training courses, which they consider to be of the utmost importance for the quality of their professional performance. Professional development is designated by almost all teachers enquired as the main motivating factor for joining teachers training courses. A large majority of teachers believe that the leaders of their schools recognize the in-service training they attend.